Pertubuhan Arkitek Malaysia (PAM): ACSR COUNTRY REPORT 2014/2015 - Mohd Nawawi, Norwina (2015)
Updated report of the events and activities in Malaysia with regard to aspects of social responsibility that architects can contribute. For Malaysia, the update govern the government initiatives, PAM initiative as an organisation, the school of architecture in respective universities, as well as an individual architect initiative.For 2014/2015 the report covers the 2014 end of year big flood on the East Coast, the Sabah Earthquake, the prevailing Housing, Homeless and Health issues as well as the extra mile respective organisation deliver their social responsibility